Red cell membrane skeletal changes in marathon runners - Jordan, J.; Kiernan, W.; Merker, H. J.; Wenzel, M.; Beneke, R. (International Journal of Sports Medicine, 1998)
Hemolysis in endurance exercise may be related to structural changes in red blood cell (RBC) membrane skeletal proteins. To test this hypothesis, we studied 13 male subjects before and after a marathon race. RBC membrane skeletons were observed with scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Plasma haptoglobin was measured. RBCs were affixed on poly-l-lysine coated glass supports for SEM and copper grids with formvar were prepared for TEM. Cytoplasmatic materials and lipid membranes were extracted with Triton-X-100 solution. TEM specimens were negatively stained and air dried. For SEM, the remaining RBC membrane skeletons were fixed, postfixed and sputtered with platinum. RBC membrane skeletal areas on SEM micrographs were measured by digitizer table planimetry. No RBC changes were observed with TEM. On the other hand, SEM showed disrupted RBC membrane skeletons. Furthermore, there appeared to be a loss of membrane material in RBC after the race, compared to RBC before the race. RBC membrane skeletal areas were increased by 30% (p<0.01). Hemolysis was indicated by a 57% decrease in plasma haptoglobin values (p<0.001). Thus, structural changes in RBC membrane skeletons occur after a marathon race. These changes can be identified with SEM but not with TEM. They may be related to increased susceptibility to chemical and physical stress and may contribute to hemolysis in endurance exercise.